Subphthalocyanines Axially Substituted with a Tetracyanobuta-1,3-diene-Aniline Moiety: Synthesis, Structure, and Physicochemical Properties - Winterfeld, Kim; Lavarda, Giulia; Guilleme, Julia; Sekita, Michael; Guldi, Dirk Michael; Torres, Tomas; Bottari, Giovanni (Journal of the American Chemical Society, 2017)
A 1,1,4,4-tetracyanobuta-1,3-diene (TCBD)-aniline moiety has been introduced, for the first time, at the axial position of two subphthalocyanines (SubPcs) peripherally substituted with hydrogen (H12SubPc) or fluorine atoms (F12SubPc). Single-crystal X-ray analysis of both SubPc-TCBD-aniline systems showed that each conjugate is a racemic mixture of two atropisomers resulting from the almost orthogonal geometry adopted by the axial TCBD unit, which were separated by chiral high-performance liquid chromatography. Remarkably, the single-crystal X-ray structure of one atropisomer of each SubPc-TCBD-aniline conjugate has been solved, allowing to unambiguously assign the atropisomers’ absolute configuration, something, to the best of our knowledge, unprecedented in TCBD-based conjugates. Moreover, the physicochemical properties of both SubPc-TCBD-aniline racemates have been investigated using a wide range of electrochemical as well as steady-state and time-resolved spectroscopic techniques. Each of the two SubPc-TCBD-aniline conjugates presents a unique photophysical feature never observed before in SubPc chemistry. As a matter of fact, H12SubPc-TCBD-aniline showed significant ground-state charge transfer interactions between the H12SubPc macrocycle and the electron-withdrawing TCBD unit directly attached at its axial position. In contrast, F12SubPc-TCBD-aniline gave rise to an intense, broad emission, which red shifts upon increasing the solvent polarity and stems from an excited complex (i.e., an exciplex). Such an exciplex emission, which has also no precedent in TCBD chemistry, results from intramolecular interactions in the excited state between the electron-rich aniline and the F12SubPc π-surface, two molecular fragments kept in spatial proximity by the “unique” three-dimensional geometry adopted by the F12SubPc-TCBD-aniline. Complementary transient absorption studies were carried out on both SubPc-TCBD-aniline derivatives, showing the occurrence, in both cases, of photoinduced charge separation and corroborating the formation of the aforementioned intramolecular exciplex in terms of a radical ion pair stabilized through-space.
CRIS-Team Scopus Importer:2022-04-14